Connecting with your kids - Smith, Timothy (Minneapolis : Bethany House, 2005)
"Connecting With Your Kids challenges life's frantic pace and offers helpful solutions to slowing down and developing the perfect pulse for individual families"--Provided by publisher.
Restless families -- Why do we rush? -- On the run -- The heart of the matter -- Turning your hearts toward each other -- The four heartprints -- Parenting a cruiser -- Parenting a walker -- Parenting a runner -- Parenting a biathlete -- Making time -- Malibu Marsha -- Kingdom kids -- the refreshing family -- Family heartprint.
Includes bibliographical references.
Keywords: Parenting; Parent and child; Families